Farmer's participation in sustainable agricultural development under highland in royal project area, Chiang Mai Province - Rungsun Kruekum (2018)
The objectives of this study were to 1) identify the situation of farmer's participation in the sustainable agricultural development (SAD) project under the Royal Project in highland area, 2) identify the relationships between factors and the participation of highland farmers in the SAD project, and 3) identify problems, threats and suggestions related to their participation. Using multi-stage sampling, 399 SAD farmers in Chiang Mai province were purposively selected. It was found that the participation level of farmers was moderate. Such independent variables as benefits from the SAD project, land holding size, involvement in agricultural development activities, and education level were statistically related to their participation in SAD project at the .05 level of significance. The significant problems of farmers participation were time constraints, lack of knowledge about the benefit of participation, and lack of appropriate public relations. Getting farmers involved in community project organizations was suggested by the farmers. In addition, the government or Royal Project should provide knowledge about benefit of participation for farmers, and the community leaders should be allowed to participate in development organization. Furthermore, the suggestions of the researcher were to train farmers more about project monitoring and evaluation. It was significant to persuade the farmers to participate in any arranged activities.